Continuous-flow columns packed with zero-valent iron and iron sulfide as a feasible strategy to remediate the persistent contaminant nitroguanidine - Youngjae Yu; Erika E. Rios-Valenciana; Robert A. Root; Reyes Sierra-Alvarez; Jon Chorover; Jim A. Field (Defence Technology)
The insensitive munitions compound nitroguanidine (NQ) is used by the U.S. Army to avoid unintended explosions. However, NQ also represents an emerging contaminant whose environmental emissions can cause toxicity toward aquatic organisms, indicating the need for effective remediation strategies. Thus, we investigated the feasibility of treating water contaminated with NQ in continuous-flow columns packed with zero-valent iron (ZVI) or iron sulfide (FeS). Initially, the impact of pH on NQ transformation by ZVI or FeS was evaluated in batch experiments. The pseudo first-order rate constant for NQ transformation (k1, NQ) by ZVI was 8–10 times higher at pH 3.0 compared to pH 5.5 and 7.0, whereas similar k1, NQ values were obtained for FeS at pH 5.5–10.0. Based on these findings, the influent pH fed to the ZVI- and FeS-packed columns was adjusted to 3.0 and 5.5, respectively. Both reactors transformed NQ into nitrosoguanidine (NsoQ). Further transformation of NsoQ by ZVI produced aminoguanidine, guanidine, and cyanamide, whereas NsoQ transformation by FeS produced guanidine, ammonium, and traces of urea. ZVI outperformed FeS as a reactive material to remove NQ. The ZVI-packed column effectively removed NQ below detection even after 45 d of operation (490 pore volumes, PV). In contrast, NQ breakthrough (removal efficiency <85%) was observed after 18 d (180 PV) in the FeS-packed column. The high NQ removal efficiency and long service life of the ZVI-packed column (>490 PV) suggest that the technology is a promising approach for NQ treatment in packed-bed reactors and in situ remediation.